Propuesta de un plan estratégico para el colegio particular de bachillerato internacional Antonio Peña Celi de la Ciudad de Loja - García Calle, Germania Verónica (2017)
The following thesis degree is about propose of Strategic Plan for Private School International Baccalaureate Antonio Peña Celi city in Loja. To do this research, the investigation was conducted to know the current situation of the educational institution, considering different aspects. During this investigation, an interview was applied to the company manager, 25 surveys teachers and 171 students to know their point of view concerning the political, strategic, people, resources, partnerships, leadership and processes handled at school. According to the results, it has proposed a strategic plan that focuses on 4 strategic objectives that include problem, goal, goal, tactics, strategies, activity, budget, responsible; these objectives were determined after an external and internal analysis through SWOT matrix and high-impact matrix. Finally conclusions and recommendations which were reached in order to propose and solve the problems facing the organization and take advantage of opportunities offered by the market to grow and strengthen presented.